Siblings of children with complex care needs: their perspectives and experiences of participating in everyday life. (19th May 2016) - Woodgate, R. L.; Edwards, M.; Ripat, J. D.; Rempel, G.; Johnson, S. F.
Summary: Background: Participating in everyday life is essential to the healthy development and emotional well‐being of children. However, little is known about siblings of children with complex care needs (CCN), and their perspectives and experiences of participating in everyday life. The aim of this paper is to present research findings that add to our understanding of how siblings of children with CCN view and experience participation in everyday life. Methods: To arrive at a detailed and accurate understanding of the siblings' perspectives and experiences, we used the qualitative research design of ethnography. Sixteen siblings (seven brothers, nine sisters) of children with CCN were recruited. The siblings ranged in age between 7 and 25 years, with a mean age of 14 years. All siblings took part in opened‐ended interviews and completed ecomaps to describe how they participate. Five siblings also took part in the photovoice method. Analysis involved several iterative steps, congruent with ethnography. Results: Four main themes emerged as follows: (1) participation is about being part of a group; (2) it feels good; (3) I love my sibling but…; and (4) promoting participation. Siblings of children with CCN identified challenges to participation and also described ways that they participate that relate to the care of their sibling. Conclusions: Siblings prioritized the relationship with their sisters and brothers with CCN in their life, and a great deal of their participation was chosen with their sibling in mind. Sibling‐to‐sibling relationships were distinct and meaningful and, as a result, participation was always done mindfully and with the family needs at the forefront. Nonetheless, clinicians caring for children with CCN must keep in mind the challenges that siblings of children with CCN experience and provide strategies to siblings that will help to promote their participation in everyday life.